Geospatial documentation of affective perceptions toward multilingual signage in Baubau’s heritage tourism landscape - Oda, Sukur; Duli, Akin; Lukman, Lukman (Edelweiss Applied Science and Technology, 2025)
This study examines tourists’ affective perceptions of multilingual public signage in Baubau’s heritage tourism landscape and how different language choices shape their engagement with the place. A semantic differential (SD) survey was distributed to 204 domestic and international visitors, who evaluated photographic stimuli representing Wolio (indigenous), Indonesian, English, and mixed-language signage across the dimensions of Evaluation, Potency, and Activity on a 7-point bipolar scale. Geospatial documentation of signage locations was incorporated to contextualise these perceptual responses within the physical tourism landscape. The results show a consistent descriptive trend in which Wolio signage received the highest mean rating (M = 1.98), followed by Indonesian (M = 1.88) and mixed-language signs (M = 1.78), while English received the lowest rating (M = 1.50). Although the repeated-measures ANOVA produced a marginal p-value (0.059), the overall trend suggests that indigenous and national languages elicit stronger emotional engagement from visitors than the global lingua franca. These findings underscore the symbolic and cultural value of Wolio and Indonesian in shaping the visitor experience, enhancing practical insights for planning multilingual signage, destination branding, and culturally sustainable tourism communication.